Application of the Modified Fractal Signature Method for Terrain Classification from Synthetic Aperture Radar Images - Malamou, A.; Pandis, C.; Frangos, P.; Stefaneas, P.; Karakasiliotis, A.; Kodokostas, D. (Elektronika ir Elektrotechnika, 2014)
In this paper the Modified Fractal Signature (MFS) method is applied to real Synthetic Aperture Radar (SAR) images provided to our research group by SET 163 Working Group on SAR radar techniques. This method uses the ‘blanket’ technique to provide useful information for SAR image classification. It is based on the calculation of the volume of a ‘blanket’, corresponding to the image to be classified, and then on the calculation of the corresponding Fractal Area curve and Fractal Dimension curve of the image. The main idea concerning this proposed technique is the fact that different terrain types encountered in SAR images yield different values of Fractal Area curves and Fractal Dimension curves, upon which classification of different types of terrain is possible. As a result, a classification technique for five different terrain types (urban, suburban, rural, mountain and sea) is presented in this paper. DOI: http://dx.doi.org/10.5755/j01.eee.20.6.7281